Secretory cycle of the Dufour's gland in workers of the bumble bee Bombus terrestris L-(Hymenoptera : Apidae, Bombini) - Abdalla, Fábio Camargo [UNESP]; Velthuis, H.; Duchateau, M. J.; Cruz-Landim, Carminda [UNESP] (Brill Academic Publishers, 1999)
The Dufour's gland of Bombus terrestris workers, of different ages and with varying degrees of ovary development, was studied with the aim to verify its involvement in reproduction. Measurements of the diameter and the length of the gland were made using an ocular micrometer adapted to a microscope. Transmission electron microscopy was used to study the morphology of the secretory cells and to analyze the secretory cycle. The glandular cells were considered to be near type II cells of NOIROT and QUENNEDEY (1974), a type that has not been described before in Hymenopterans. The results show that there is a correlation between the degree of ovary development and Dufour's gland activity of workers. The diameter of the gland and the secretory cell activity increased with increasing oocyte size in the ovary. Regressive conditions of the gland were observed, which are probably related to increasing worker age. To elucidate the production and releasing process of the secretion and to establish its precise function, a comparative analysis of the secretion process of the Dufour's gland of queens and workers is needed.
Keywords: Bombus terrestris; Bumble bee; Dufour's grand; egg marking; workers